TWEAK/Fn14 Axis-Targeted Therapeutics: Moving Basic Science Discoveries to the Clinic - Cheng, Emily; Armstrong, Cheryl L.; Galisteo, Rebeca; Winkles, Jeffrey A. (Frontiers in Immunology, 2013)
The TNF superfamily member TWEAK (TNFSF12) is a multifunctional cytokine implicated in physiological tissue regeneration and wound repair. TWEAK is initially synthesized as a membrane-anchored protein, but furin cleavage within the stalk region can generate a secreted TWEAK isoform. Both TWEAK isoforms bind to a small cell surface receptor named Fn14 (TNFRSF12A) and this interaction stimulates various cellular responses, including proliferation and migration. Fn14, like other members of the TNF receptor superfamily, is not a ligand-activated protein kinase. Instead, TWEAK:Fn14 engagement promotes Fn14 association with members of the TRAF family of adapter proteins, which triggers activation of various signaling pathways, including the classical and alternative NF-κB pathways. Numerous studies have revealed that Fn14 gene expression is significantly elevated in injured tissues and in most solid tumor types. Also, sustained Fn14 signaling has been implicated in the pathogenesis of cerebral ischemia, chronic inflammatory diseases, and cancer. Accordingly, several groups are developing TWEAK- or Fn14-targeted agents for possible therapeutic use in patients. These agents include monoclonal antibodies, fusion proteins, and immunotoxins. In this article, we provide an overview of some of the TWEAK/Fn14 axis-targeted agents currently in pre-clinical animal studies or in human clinical trials and discuss two other potential approaches to target this intriguing signaling node.